2014
DOI: 10.1002/cphc.201402806
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Clock Reactions

Abstract: Autocatalytic systems are sometimes designated as clock reactions or reactions that exhibit clock behavior. To resolve the recent dispute over the term clock reaction, we describe a new approach to classify systems featuring clock behavior into three distinct groups: substrate-depletive clock reactions, autocatalysis-driven clock reactions, and systems that have pseudo clock behavior. Many of the well-known classical and recently discovered reactions can conveniently be put into these categories. We also provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 43 publications
0
73
0
1
Order By: Relevance
“…When parallel experiments were performed under ''exactly the same experimental conditions'' in the chlorite-thiosulfate 1 and iodide-chlorite 2 reactions, the products of chlorine dioxide and iodine, respectively, appeared after a fairly long but strongly irreproducible time lag, making the reactions later be classified as crazy-clock reactions. 3 The phenomenon became the subject of great interest when Soai et al reported the discovery of asymmetric amplification in an autocatalytic reaction in 1995, 4 followed by their subsequent study on the stochastic nature of enantiomerically enriched pyrimidyl alkanol obtained from the reaction of pyrimidine-5carbaldehyde and diiodopropylzinc. 5 Since then, these reactions have became the prototypes of stochastic chemical systems.…”
Section: Introductionmentioning
confidence: 99%
“…When parallel experiments were performed under ''exactly the same experimental conditions'' in the chlorite-thiosulfate 1 and iodide-chlorite 2 reactions, the products of chlorine dioxide and iodine, respectively, appeared after a fairly long but strongly irreproducible time lag, making the reactions later be classified as crazy-clock reactions. 3 The phenomenon became the subject of great interest when Soai et al reported the discovery of asymmetric amplification in an autocatalytic reaction in 1995, 4 followed by their subsequent study on the stochastic nature of enantiomerically enriched pyrimidyl alkanol obtained from the reaction of pyrimidine-5carbaldehyde and diiodopropylzinc. 5 Since then, these reactions have became the prototypes of stochastic chemical systems.…”
Section: Introductionmentioning
confidence: 99%
“…10 It consists of a slow direct reaction between the reactants producing the autocatalyst (usually iodide ion) which then gives rise to the appearance of iodine by the Dushman reaction. 12 When the rate of production of iodine overtakes that of its removal the appearance of iodine rings the bell for the clock behavior. The relative rate difference of the substrate-iodine reactions recently provided an opportunity to classify clock reactions.…”
Section: Introductionmentioning
confidence: 99%
“…It is well understood that removal of an inhibitor without autocatalysis can result in rapid production of a species after a time lag. 17,18 However there is an important difference in these two cases. With autocatalysis, both the rate of production of acid and the rate of removal of substrate, aqueous ester, accelerate in time.…”
Section: Resultsmentioning
confidence: 99%